Menjaga Disiplin di Tengah Gempuran Budaya Asing: Dampak Korean Wave pada Karakter Gen Z di Pesantren - Suhilmiati, Endhang; Khoir, Nailah Ummil; Fadlullah, Muhammad Endy (FKDP (Forum Komunikasi Dosen Peneliti), 2025)
This study aims to examine the influence of the Korean Wave on the disciplinary character of Generation Z high school students at Yayasan Pondok Pesantren Bustanul Makmur. The Korean Wave, or Hallyu, is a global phenomenon encompassing the dissemination of South Korean popular culture—such as music (K-Pop), drama, fashion, and lifestyle—which has gained significant popularity among adolescents, including students in Islamic boarding schools. This phenomenon is believed to exert both positive and negative impacts on character development, particularly in relation to discipline. The research employed a quantitative method with an explanatory survey approach. The sample consisted of 70 female students aged 15–18 years (Gen Z) who are enthusiasts of the Korean Wave. Data collection techniques included observation, interviews, documentation, and questionnaires. The data were analyzed using simple linear regression with the assistance of SPSS 27.0. The findings indicate a significant influence of the Korean Wave on the disciplinary character of Gen Z students at Yayasan Pondok Pesantren Bustanul Makmur, with a significance value of < 0.05. The magnitude of this influence is reflected in the coefficient of determination (R Square) of 0.467 or 46.7%, meaning that 46.7% of the variation in disciplinary character is explained by the intensity of engagement with the Korean Wave, while the remaining percentage is influenced by other factors. The study concludes that although the Korean Wave contributes positively to cultural awareness and creativity, it may also affect students’ discipline if not approached wisely. Therefore, strengthening character education that is adaptive to global cultural developments is essential within the pesantren environment.